Unprecedented Utilization of Pelargonidin and Indole for the Biosynthesis of Plant Indole Alkaloids. (28th January 2016) - Warskulat, Anne‐Christin; Tatsis, Evangelos C.; Dudek, Bettina; Kai, Marco; Lorenz, Sybille; Schneider, Bernd
Abstract: Nudicaulins are a group of indole alkaloid glycosides responsible for the color of yellow petals of Papaver nudicaule (Iceland poppy). The unique aglycone scaffold of these alkaloids attracted our interest as one of the most unusual flavonoid‐indole hybrid structures that occur in nature. Stable isotope labeling experiments with sliced petals identified free indole, but not tryptamine orl ‐tryptophan, as one of the two key biosynthetic precursors of the nudicaulin aglycone. Pelargonidin was identified as the second key precursor, contributing the polyphenolic unit to the nudicaulin molecule. This finding was inferred from the temporary accumulation of pelargonidin glycosides in the petals during flower bud development and a drop at the point in time when nudicaulin levels start to increase. The precursor‐directed incorporation of cyanidin into a new 3′‐hydroxynudicaulin strongly supports the hypothesis that anthocyanins are involved in the biosynthesis of nudicaulins. Abstract : Flower power : Nudicaulins, a group of unique indole alkaloids, are the pigments of yellow petals of Papaver nudicaule (Iceland poppy). Isotope labeling, metabolic profiling, and precursor‐directed biosynthetic (PDB) experiments indicated the origin of nudicaulins from free indole and pelargonidin as the key precursors.